Social Dimensions of Housing Heterogeneity: A Pathway to Understanding Market Mechanics and Valuation - Vanags Janis; Jansons Leo; Geipele Ineta; Stāmure Iveta; Sanchaniya Rashmi Jaymin (Real Estate Management and Valuation)
The composition of the housing market is shaped by the social dimensions of buyer heterogeneity, prompting households to prioritize housing development to fulfill their needs efficiently. Both quantitative and qualitative dimensions of housing heterogeneity in transactions stem from the different characteristics, needs, and incomes of residents in different areas. The relevance of this research lies in understanding the social dimensions driving housing diversity among buyers and sellers. In a market economy, meeting the evolving needs of market participants is crucial. Consequently, stakeholders in the housing market focus on understanding buyer needs, changing trends, and adapting to the heterogeneity of the housing options. The housing market, characterized by significant information asymmetry, underscores the importance of comprehensively studying the social dimensions of housing diversity, particularly its impact on market value and transaction prices. Viewing households as heterogeneous social systems highlights the dominance of the social dimension in the housing market, necessitating a comprehensive exploration of its quantitative and qualitative aspects. Findings can inform managerial decisions to mitigate information asymmetry, improve housing availability, stabilize prices, and improve the market value of properties.